Dampak Pelatihan Public Speaking terhadap Efektivitas Pelayanan Publik Aparatur Kecamatan Bekasi Utara: Evaluasi Pra dan Pasca Pelatihan - Devy Putri Kussanti; Fifit Fitriansyah; Parlin Harbet; Jaka Atmaja (Journal of Entrepreneurship and Community Innovations, 2026)
This community service activity aims to improve the effectiveness of public services provided by the staff of Bekasi Utara Subdistrict through public speaking training. This initiative is motivated by the fact that the public speaking and public service communication skills of some staff members have not yet been fully optimized, which affects the effectiveness of information delivery, the quality of interactions with the community, and the handling of public complaints. The staff still face challenges in delivering messages clearly, systematically, and persuasively, thereby increasing the potential for miscommunication in the service process. In addition, the level of self-confidence among staff members in communicating in public settings has not been fully developed, which influences their professionalism and the quality of services provided. The method is a descriptive qualitative approach through observation, interviews, and documentation. The results indicate that the staff of Bekasi Utara Subdistrict not only appreciated the public speaking training but also strongly supported the continuation of similar community service activities in the future. This training was found to have a positive impact on enhancing self-confidence, clarity of message delivery, and the overall communication skills of staff members in carrying out their public service duties.